The Importance of the Human Mass Balance Study in Regulatory Submissions - Paola Coppola; Anita Andersson; Susan Cole (Wiley, 2019)
The human mass balance study is a key study in the Clinical Pharmacology package of new drug applications. This study, along with the mass balance studies in toxicology species, provides essential information on the exposure of the parent compound and metabolites. Despite current regulatory guidance and previous publications, a lack of this study, or deficiencies in the study, are still seen in regulatory submissions today. This restricts the assessment of the benefit/risk in all populations and on the potential for drug-drug interactions leading to unnecessary precautions in the label. A review of new drug applications identifies a number of examples of inadequate characterization of circulating drug‐related components or of elimination pathways, with questions raised during the regulatory review. In light of this, new insight is given on what is required from the mass balance study and on how to ensure sufficient information is captured.